Analysis of disordered regions of AIMR1/p43 protein from human multisynthetase complex with bioinformatics methods - Limanska, T. S.; Nyporko, A.Yu.; Kornelyuk, A. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
Features of the secondary structure and locations of the disordered regions in the structure of AIMRI protein — component of the human multisynthetase complex are investigated with several in silico approaches. It is revealed that the longest part of the protein disclosed to fold into a disordered structure is located from 103 to 148 amino acid residue. Interestingly, within this region (from about 121 to residue 140), the presence of α-helix is also possible. This seeming contradiction is simply explained by the saturation of the appropriate region by both lysine residues (marker of disordered regions of proteins) and glutamate residues (typical marker of α-helical elements). With high probability, we can assume that this spiral is metastable, i. e., moving to a disordered state and back due to natural fluctuations of the protein molecule.